Efficacy and safety of infliximab as continuous or intermittent therapy in patients with moderate‐to‐severe plaque psoriasis: results of a randomized, long‐term extension trial (RESTORE2). (5th June 2013) - Reich, K.; Wozel, G.; Zheng, H.; van Hoogstraten, H.J.F.; Flint, L.; Barker, J.
Abstract : What's already known about this topic? Continuous maintenance therapy with infliximab 5 mg kg −1 every 8 weeks is effective for moderate‐to‐severe plaque‐type psoriasis. What does this study add? For patients receiving an intermittent infliximab therapy regimen, the incidence of serious infusion‐related reactions was greater than expected during reinduction. Clinicians should avoid using intermittent therapy in this patient population. Summary: Background: Continuous maintenance therapy with infliximab 5 mg kg −1 every 8 weeks is effective for moderate‐to‐severe plaque‐type psoriasis. Objectives: To evaluate the efficacy and safety of continuous vs. intermittent infliximab maintenance therapy. Methods: RESTORE2 was a long‐term extension of RESTORE1. At baseline of RESTORE2, eligible patients who had received infliximab for 26 weeks and achieved Psoriasis Area and Severity Index (PASI) 75 in RESTORE1 were rerandomized 1 : 1 to continuous therapy (infliximab 5 mg kg −1 every 8 weeks) or intermittent therapy (no infliximab until > 50% loss of PASI improvement). Safety and efficacy assessments occurred throughout the study. Results: In total, 222 patients were randomized to receive continuous therapy, and 219 to intermittent therapy. More serious infusion‐related reactions occurred with intermittent therapy (8/219 patients, 4%) than with continuous therapy (1/222 patients, < 1%), leading the sponsor to terminate the study. The mean duration of exposure to infliximab was 40·12 weeks (SD 27·55) with a mean of 5·8 infusions (range 0–16) for continuous therapy and 22·78 weeks (SD 22·98) with a mean of 3·4 infusions (range 0–16) for intermittent therapy. Although no formal efficacy analyses were conducted, continuous therapy led to greater PASI 75 at week 52 in the continuous group (81/101, 80%) than in the intermittent group (39/83, 47%); several other efficacy measures demonstrated similar patterns. Conclusions: For patients with moderate‐to‐severe plaque‐type psoriasis, continuous therapy with infliximab may be more effective than intermittent therapy. The incidence of serious infusion‐related reactions in the intermittent group suggests that clinicians should avoid intermittent therapy in this population.